Problematic Aspects of the Activities of Chiune (Sempo) Sugihara in Kaunas in 1939 and 1940 - Ivanovas, Bernaras (Genocidas ir rezistencija, 2001)
The activities of the Japanese consul, Sempo Sugihara, in Kaunas in 1939 and 1940 still raises many questions. This does not, however, prevent us from realizing what enormous efforts he took to save thousands of Jews. Employing all possible means, including using officials from the Polish secret service and even a duplicate seal, which might have served as the grounds for his dismissal from the post in 1947, he saved hundreds and even thousands of people. Meanwhile, the attitude of his wife Yukiko Sugihara to the risks he took, which were not always correct, can be explained by the status of women in traditional Japanese society: her husband did not tell her about many things, something which she emphasized many times.Sugihara's story shows that refugees sought actively the means to save their lives and help others; in the historiography of the Holocaust the victims are often described as being passive.Bearing in mind the attitude of Sugihara and the Japanese government towards the Jews, the role Japan played during the Second World War should be examined anew, which would open a new chapter in the study of the Holocaust.
Keywords: Chiune (Sempo) Sugihara; Japan; Poland; Jews